Preliminary study on rotary ultrasonic machining of CFRP/Ti stacks - Cong, Weilong; Pei, Zhijian J.; Treadwell, C. (My University, 2014)
Reported drilling methods for CFRP/Ti stacks include twist drilling, end milling, core grinding, and their derived methods. The literature does not have any report on drilling of CFRP/Ti stacks using rotary ultrasonic machining (RUM). This paper, for the first time, reports a study on drilling of CFRP/Ti stacks using RUM. It also compares results on drilling of CFRP/Ti stacks using RUM with reported results on drilling of CFRP/Ti stacks using other methods. When drilling CFRP/Ti stacks using RUM, cutting force, torque, and CFRP surface roughness were lower, hole size variation was smaller, CFRP groove depth was smaller, tool life was longer, and there was no obvious Ti exit burr and CFRP entrance delamination. Ti surface roughness when drilling of CFRP/Ti stacks using RUM was about the same as those when using other methods.
Keywords: CFRP composite; Drilling; Grinding; Rotary ultrasonic machining; Stack; Titanium